A general template to configure multi-criteria problems in Ubiquitous GDSS - Carneiro, João (2015)
The study of multi-criteria problems adapted to the context of Ubiquitous Group Decision Support Systems (UbiGDSS) is covered in the literature through very different perspectives and interests. There are scientific studies related to the multi-criteria problems that lie across argumentation-based negotiation, multi-agent systems, dialogues, etc. However, to perform most of these studies, a high amount of information is required. The usage of so much data or information that is difficult to collect or configure can bring good results in theoretical scenarios but can be impossible to use in the real world. In order to overcome these issues, we present in this paper a general template to configure multi-criteria problems adapted for the contexts of UbiGDSS that intends to be easy and fast to configure, appellative, intuitive, permits to collect a lot of data and helps the decision-maker transmitting his beliefs and opinions to the system. Our proposal includes three sections: Problem Data, Personal Configuration and Problem Configuration. We have developed a prototype with our template with the purpose to simulate the configuration of a multi-criteria problem. We invited real decision-makers to use our prototype in a simulated scenario and asked to them to fulfil a survey in the end in order to study our hypotheses. Our general template achieved good results and proved to be very perceptible and fast to configure.